FRI0588 Comparing The Burden of Illness of Patients with Tophaceous and Non-Tophaceous Gout in France, Germany, Italy, Spain, and The UK. (15th July 2016) - Khanna, P.; Tafesse, E.; Baumgartner, S.; Walker, A.; Morlock, R.
Abstract : Background: Gout is a common inflammatory arthritis and its worldwide prevalence is increasing. EULAR and American College of Rheumatology guidelines recommend a target sUA <6 mg/dL, with a target of <5 mg/dL in those with more severe symptomatic disease. Patients with significant crystal burden are assumed to have higher humanistic and economic burden of illness. Objectives: To describe patient and treatment characteristics and resource utilization in gout patients with and without tophi. Methods: Data were assessed from a survey of physicians and in-depth patient chart audits from France, Germany, Italy, Spain and the UK. Severity of gout was measured by physician global assessment. Flares, organ/joint damage and tophi were abstracted from the clinical chart. Type/dose of xanthine oxidase inhibitor, length of current treatment, physician type and patient sociodemographic factors were identified. Anonymized patients were included. Patients with a diagnosis of tophaceous gout were compared to all other gout (non-tophaceous) patients. Demographic characteristics and comorbidities, sUA levels, and use of colchicine for acute flares during the 12-month study period were compared using chi-square or Fisher's exact tests. Results: Of the 1260 patients identified with gout, 327 (25.95%) had physician-confirmed tophaceous gout and 933 (74.05%) had non-tophaceous gout. Patients with tophi were older (62.3 vs 58.6 years old; p<0.001), had gout for a slightly longer period of time (2.8 vs 2.5 years; p<0.001), reported more flares (3.4 vs 1.7 per year; p<0.001), and were more likely to have joint damage (45.3% vs 10.5%; p<0.001). There were significantly higher levels of comorbidities in patients with tophi including cardiovascular disease (p<0.001), chronic obstructive pulmonary disease (p<0.001), congestive heart failure (p<0.001), diabetes (p=0.011), depression (p=0.001), hypertension (p<0.001), osteoarthritis (p<0.001) and Stage III (p<0.001) and Stage V (p=0.016) chronic kidney disease. Patients with tophi were more likely to be treated with a urate-lowering therapy (87.5% vs 78.6%; p<0.001). Patients with tophi were less likely to be using allopurinol (56% vs 68%; p<0.001) and more likely to be treated with febuxostat (22.9% vs 7.9%). There was no difference in the use of NSAIDs; however, patients with tophi were more likely to take colchicine (46.5% vs 33.7%; p<0.001) and steroids (27% vs 10%; p<0.001). Patients with tophi were less likely to reach the ideal treatment goal of sUA targets of <6 mg/dL and no flares (17% vs 27%; p<0.001) or <5 mg/dL and no flares (6% vs 14%; p<0.001). Patients with tophi made more gout-related office visits (6.07 vs 4.51; p<0.001) and a greater proportion made ≥1 gout-related emergency visit (27.2% vs 9.5%; p<0.001), hospitalization (12.8% vs 3%; p<0.001) or had a gout- related surgery (3.1 vs 1.2; p=0.022). Conclusions: Patients with tophaceous gout have significantly greater burden of disease and greater frequency of comorbidities than patients with non-tophaceous gout. Preventing the development of tophi or resolving crystal burden by treating to guideline targets remains a rarely achieved goal for patients with and without tophi. Acknowledgement: This study was funded by AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: P. Khanna Grant/research support from: AstraZeneca, E. Tafesse Employee of: AstraZeneca, S. Baumgartner Employee of: Ardea Biosciences, a member of the AstraZeneca Group, A. Walker Employee of: AstraZeneca, R. Morlock Employee of: Ardea Biosciences, a member of the AstraZeneca Group